The Existence of Tourism Resources in the Coastal Area of Pantai Indah Bosowa, Makassar City - Ayu Andira; Hasriyanti H; Maddatuang M (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Tourism is a sector that is currently developing and has even become a global phenomenon. Indonesia's marine and coastal areas have the highest biodiversity in the world. The coastal area of Makassar city is located in the Tanjung Bunga Metro Area, Tamalate District, Makassar City, South Sulawesi. This research is a type of qualitative research with the sampling technique used is purposive sampling with data collection techniques used, namely 1) observation techniques, 2) interview techniques, 3) documentation techniques. The results show that the coastal area of Indah Bosowa has qualified potential both in terms of beauty and others, the beautiful beach of Bosowa is considered a very new beach considering the year it was built around 2020 so that tourism management needs to be done.